Evaluasi Kesehatan pada Aspek Kinerja Keuangan Koperasi Simpan Pinjam Bumdesma Kembar Sejahtera - MIRANTHI, NAMIRA PUTRI; NAJMUDDIN, MOHAMMAD ILHAM; WIRATNO, ADI; -, IRIANING SUPARLINAH (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study evaluates the health of the financial performance aspects of the BUMDesma “Kembar Sejahtera” Saving and Loan Cooperative (KSP) for the year 2023. Using a descriptive quantitative approach, the analysis was based on the technical guidelines outlined in the Technical Guidelines of the Deputy for Cooperatives No. 15 of 2021, focusing on key financial performance aspects such as profitability, financial management, and financial sustainability. The findings show that the cooperative is classified as “healthy” with an overall score of 83.33. However, certain aspects, including asset profitability and asset growth, were categorized as “less healthy”, indicating the need for improved asset utilization and better growth strategies.